HIV incidence among sexually active young males and females in Kisumu County, Western Kenya - John Owuoth; Chiaka Nwoga; Valentine Sing’oei; Adam Yates; June Otieno; Erica Broach; Qun Li; Zebiba Hassen; Seth Frndak; Michelle Imbach; Leigh Anne Eller; Mark Milazzo; et al. (PLoS ONE, 2026)
Introduction HIV prevalence in Kisumu County, Kenya, is over four times the national average. We estimated HIV incidence among adults with multiple sexual partners and identified risk factors associated with HIV acquisition. Methods We enrolled adults aged 18–35 years reporting ≥2 sexual partners in the prior 3 months, recruiting primarily from villages with fisherfolk. HIV counseling and testing were performed every 3 months for up to 24 months. Demographic, health, sexual, and behavior questionnaires were administered every 6 months. Enrollment characteristics were compared between participants who did and did not acquire HIV using chi-squared tests. Bivariable Cox proportional hazards models estimated hazard ratios (HRs) and 95% confidence intervals (CIs) for potential risk factors. Results Between January 2017 and August 2021, 619 participants without HIV were enrolled, of whom 45% were female, 47% were ≥25 years old, 66% were single or widowed, and 46% had some secondary education. Eleven HIV seroconversions occurred over 1117.9 person-years (PY; incidence 9.84/1000 PY [95% CI: 5.22–17.03]), including eight in the first year of follow-up (13.84/1000 PY). Risk factors in unadjusted analyses included ≥4 sexual partners (HR 4.39 [95% CI 1.10-17.55]) and forced sexual activity (HR 9.15 [95% CI 1.17-71.51]). Conclusion HIV incidence was lower than expected, possibly reflecting prevention efforts or COVID-19-related behavior changes. Lower incidence in later follow-up may indicate a cohort effect from regular counseling. Increasing ART coverage and pre-exposure prophylaxis may have decreased HIV incidence in fishing communities of Western Kenya.